Cutting-edge Innovations in Oleanolic Acid Formulation (Asian Journal of Pharmaceutics (AJP), 2025)
Oleanolic acid (OA), a naturally occurring pentacyclic triterpenoid, has garnered significant attention due to itsbroad spectrum of pharmacological activities. Despite its therapeutic potential, the clinical application of OAis limited by its poor water solubility and low bioavailability, which hinder effective systemic absorption andtherapeutic efficacy. Advances in pharmaceutical formulation technologies have addressed these challenges,paving the way for enhanced delivery systems that improve OA solubility, stability, and bioavailability. Among themost promising strategies are nanoformulations, including lipid-based nanoparticles, polymer-based nanocarriers,and solid lipid nanoparticles (SLNs). Lipid-based systems such as liposomes and nanoemulsions not only protectOA from environmental degradation but also facilitate controlled release and improved skin permeability, makingthem suitable for topical delivery. Polymeric carriers and micelles offer targeted delivery and sustained drugrelease, while SLNs enhance drug loading and stability. Characterization techniques such as dynamic lightscattering, zeta potential analysis, electron microscopy, and differential scanning calorimetry ensure formulationquality, stability, and performance. These advanced delivery systems significantly improve the pharmacokineticprofile and therapeutic potential of OA.